Answer:
x = -7 ±3i
Step-by-step explanation:
(x+7)^2+9=0
Subtract 9 from each side
(x+7)^2+9-9=0-9
(x+7)^2=-9
Take the square root of each side
sqrt((x+7)^2) = ±sqrt(-9)
We know sqrt(ab) = sqrt(a) sqrt(b)
x+7 = ±sqrt(-1) sqrt(9)
We know that sqrt(-1) is the imaginary number i
x+7 = ±i *3
x+7 =±3i
Subtract 7 from each side
x+7-7 = -7 ±3i
x = -7 ±3i
Answer:
-2
Step-by-step explanation:
3 - 5 = -2
Place the dot on -2 on the number line that is on your problem as the answer. To show the steps on the number line, use your jumps to go back. For example, your starting point will be on 3, and then use your jumps to go back by 5; that means you go into the negatives. For this case, it is -2.
Answer:
I don't think so
Step-by-step explanation:
Answer:
x /\ y
1 /\ -4
2 /\ -5
3 /\ -6
4 /\ -7
... /\ ...
Step-by-step explanation: